PELAYANAN ADMINISTRASI KEPENDUDUKAN BAGI KOMUNITAS ADAT TERPENCIL (KAT) DI DESA TALANG PERIGI KECAMATAN RAKIT KULIM KABUPATEN INDRAGIRI HULU - Wika Difa Kartini; Adianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Isolated Traditional Community (ITC) is a community that still exists spread out in remote areas whose location is geographically difficult to travel and generally still lagging behind and isolated economically and socio-politically. The ITC’s community in Talang Perigi Village, Rakit Kulim District, Indragiri Hulu Regency, is an indigenous Talang Mamak tribe who is the oldest Malay ethnic tribe who has the right to development and behavior by the government. The research of this study is to how population administration and administration services to determine internal and external factors as abstracles in the procedure of population administration service. The used is qualitative research with discussing ethnography that encourages descriftive analysis to in depth interview on several reseacrch subjects. This found that in practice the procedures were is seen from: operational service that were still don’t opimal and therefore the ITC’s had difficulty understanding it, the completion time is not in accordance with established  standard, there were still costs incurred, the service products were still lacing and wrong, still lacks the facilities and infrastructute , and the competence of officers service personnal is not yet maximal. Internal factors that affect service still lack human resources and inadequate office infrastructure, as well external factor for the the ITC’s participation in population administration procedures. Keywords: Isolated Traditional Community (ITC), Excellent Service, Population Administration